Satisfaction with internal communication and hospitality employees’ turnover intention: Exploring the mediating role of organizational support and job satisfaction - Duarte, A. P. (2023)
Managing employee turnover is a key function in human resource management (HRM) that has become especially relevant given current staff shortages. The travel and tourism industry has been strongly affected, with many organizations having difficulty attracting and retaining workers. Portugal, as a prominent player in tourism, is no exception, and the workforce shortage crisis has been discussed in various forums and has attracted media attention. The present study examined hotel employees’ turnover intention and its relationship with their job satisfaction and positive perceptions of internal communication and organizational support. The proposed theoretical model included that internal communication contributes to the quality of employee–organization relationships by increasing perceived organizational support and job satisfaction, which in turn serve as sequential mediators of hotel workers’ diminished intent to leave their employer. Multiple regression analyses were performed using data collected from 12 hotels (number = 370 workers). The results support the model as they confirm that a statistically significant negative relationship exists between employees’ satisfaction with internal communication and their turnover intention. These variables are both directly and indirectly connected through perceived organizational support and job satisfaction. Implications for HRM are discussed including the importance of refining internal organizational communication to strengthen employee–organization ties.